The Macroeconomic Effects of Large Exchange Rate Appreciations - Marcus Kappler; Helmut Reisen; Moritz Schularick; Edouard Turkisch (Open Economies Review, 2013)
In this paper we study the macroeconomic aftermath of large exchange rate appreciations. Using a sample of 128 countries over the period 1960–2008, we identify 25 episodes of large nominal and real appreciations shocks. We use narrative identification of exogenous appreciation episodes and study the macroeconomic effects in a dummy-augmented panel autoregressive model.
Keywords: F4; F31; 330; Current account adjustment; Global imbalances; Leistungsbilanz; Internationales Finanzsystem